Morbidity and drug prescribing patterns at a rural primary health care center of Bangladesh (IMC Journal of Medical Science, 2019)
Background and objectives: World Health Organization (WHO) and the National Health Policy of Bangladesh have repeatedly been emphasizing on the use of essential drugs prescribed by generic names. The prescription monitoring studies provide a bridge between areas like rational use of drugs and evidence based medicine. Knowledge on distribution and burden of diseases in a community is essential for planning rational use of drugs in a community. The present study tried to determine the morbidity profile and drug prescribing practices of healthcare providers in a rural primary health care.Methods: The study was conducted at a rural health center located 50 Km north of capital city Dhaka. A semi-structured questionnaire was used for collecting data on socio-demographic conditions, clinical complaints and types of drugs prescribed. WHO prescribing indicators was used to find out the drug prescribing pattern.Results: A total of 583 patients were enrolled. Problems related to respiratory system (21.1%), musculoskeletal system (17.3%) and skin diseases (11.1%) were common reasons for visiting health centre. Oral drugs were prescribed with highest proportion (96.1%). More than half (62.6%) of the drugs were prescribed from essential drug list. About half (49.1%) were antibiotics and 45.6% of the drugs were prescribed in their generic name. Anti-microbial (64.5%), anti-peptic ulcer (43.1%) and NSAIDs (42.5%) were most frequently prescribed. Out of five WHO core prescription indicators, four were below the acceptable values.Conclusion: The study demonstrated that there is an urgent need to promote rational use of drugs among the healthcare providers.IMC J Med Sci 2018; 12(2): 50-56